Efektivitas Pelaksanaan Mediasi dalam Penyelesaian Perkara Perceraian (Studi Kasus Pengadilan Agama Kuningan dan Pengadilan Agama Majalengka) - Virgin Elvany (Uniku Law Review, 2023)
Marriage is a physical and spiritual bond that has a sacred nature, ideally it can be done once in a lifetime, but in reality many husbands and wives take court action. The formulation of the problem of this research is how mediation is regulated in religious courts according to statutory regulations, and how effective the implementation of mediation is in resolving divorce cases in the Kuningan religious court and the Majalengka religious court. The aim of this research is to determine the legal regulations and effectiveness of mediation in divorce cases at the Kuningan religious court and the Majalengka court. The research method uses empirical juridical methods. The results of the research show that divorce cases in Kuningan Regency and Majalengka Regency can be resolved through mediation in religious courts, based on Supreme Court Regulation (PERMA) Number 1 of 2016 concerning Mediation Procedures in Court. Mediation is a process that is private, confidential and cooperative in nature. solve the problem. Because the mediator as a third party helps the disputing parties in resolving the conflict and resolving or bringing their differences closer together. Therefore, the effectiveness of the mediation carried out in the two courts can be proven by the ongoing mediation which can be attended by both parties to the case. Factors that hinder the effectiveness of the law regarding mediation include one of the parties not appearing in the case, and the law enforcement factor itself which is caused by certain reasons. In conclusion, the implementation of mediation in divorce cases can be effective if both parties to the case are present so that mediation can be carried out by the mediator to achieve peace, in accordance with the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Court.   Perkawinan adalah suatu ikatan lahir batin yang bersipat suci idealnya boleh dilakukan satu kali seumur hidup, tetapi pada kenyataanya banyak suami istri yang melakukan gugatan kepengadilan. Rumusan masalah dari penelitian ini adalah bagaimana pengaturan mediasi di pengadilan agama menurut peraturan perundangan-undangan, dan bagaimana efektifitas pelaksanaan mediasi dalam penyelesaian perkara perceraian di pengadilan agama kuningan dan pengadilan agama majalengka. Tujuan dalam penelitian ini untuk mengetahui pengaturan hukum dan efektivitas pelaksanaan mediasi dalam perkara perceraian di pengadilan agama kuningan dan pengadilan majalengka. Metode penelitian dengan menggunakan metode yuridis empiris. Hasil penelitian menujukan bahwa perkara perceraian di Kabupaten Kuningan dan juga Kabupaten Majalengka dapat diselesaikan melalui mediasi di pengadilan agama, berdasarkan Peraturan Mahkamah Agung (PERMA) Nomor 1 Tahun 2016 Tentang Prosedur Mediasi Di Pengadilan, Mediasi adalah suatu proses yang bersifat pribadi, rahasia dan kooperatif dalam menyelesaikan masalah. Karena mediator selaku pihak ketiga membantu para pihak yang bersengketa dalam menyelesaikan konflik dan menyelesaikan atau mendekatkan perbedaan-perbedaannya. Oleh karena itu, efektivitas mediasi yang dilakukan dikedua pengadilan tersebut dapat dibuktikan dengan berjalanya mediasi yang dapat dihadiri oleh kedua pihak yang berperkara. Faktor yang menghambat efektivitas hukum tentang mediasi ini salah satunya salah satu pihak tidak datangnya yang berperkara, dan faktor penegak hukumnya itu sendiri yang diakibatkan oleh alasan-alasan tertentu. Kesimpulan pelaksanan mediasi dalam perkara perceraian ini dapat berjalan efektif apabila hadirnya kedua pihak yang berperkara untuk dapat dilakukannya mediasi yang dilakukan oleh mediator untuk mencapai perdamaian, sesuai dengan Peraturan Mahkamah Agung Republik Indonesia Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan.